PENGARUH STRATEGI PEMBERDAYAAN DINAS PERINDUSTRAN, PERDAGANGAN KOPERASI TERHADAP PENINGKATAN PENDAPATAN UMKM KOPERASI DI KOTA JAYAPURA - Lado, Meity; Deodata, Gratiana (DINAMIS, 2021)
This study aimed to determine the measured effect of strategy and empowerment on increasing income. The population in this study were all cooperatives registered with the Jayapura City Industry, Trade, and Cooperatives Service. Sampling using the purposive sampling method based on recommendations from the relevant agencies to obtain a total sample of 4 cooperatives—data collection techniques using a questionnaire. The analytical method used in this study is instrument analysis, classical assumption analysis, and hypothesis analysis using the SPSS 26 program. The results of this study state that strategy and empowerment partially do not affect increasing income and that simultaneous research on process and empowerment research does not affect increasing income.